Comparative assessment of pollution control measures for urban water bodies in urban small catchment by SWMM - Liu, Jie; Zhang, Xiang; Gui, Haijiao (Frontiers in Environmental Science, 2024)
Under the current increasingly serious water pollution situation in urban, the comprehensive treatment and protecting measures in urban small catchment are the necessary step to the water pollution treatment, not only focus on the water bodies themself. In this paper, the Luojiagang river channel and its catchment in Wuhan, which has been heavily impacted by water pollution, are taken as an example for the comparative assessment of pollution control measures in order to explore the effective and sustainable schemes including the LID(Low Impact Development---LID) by using SWMM model (Storm Water Management Model---SWMM). Through the comparison of pollution treatment measures based on scenarios simulation with the baseline scenarios, it was found that the reduction effects of pollutant peak concentrations at the outlet node of Luojiagang River had the decreasing order of: the combined measures(COS)> LID control> the water diversion from Donghu Lake(WAD)>the sewage treatment(SET)>the sediment dredging(SED), and the reduction effects of total pollutant load had the decreasing order of: LID>COS>SET>SED>WAD. The results show that the control of non-point source pollution is the key for the improvement of water quality in Luojiagang River, and LID plays important role in the reduction of both pollutant peak concentrations and load. This study has the implication for the decision making of the water pollution controlling schemes in urban small catchment.